Garlic feed inclusion and susceptibility of broiler chickens to infectious bursal disease - Oladele, Omolade; Esan, Oluwaseun; Akpan, Ini; Enibe, Francis (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: This study was carried out to evaluate the effect of garlic (Allium sativum) with its immunomodulatory activity, on the susceptibility of broilers to infectious bursal disease, being an immunosuppressive disease. Materials and methods: Day-old broilers (102) were separated into 6 groups A-F of 17 each. Groups A, B and C had 0.125% of garlic-meal in feed. At 8 and 18 days of age groups A, C, D and F were administered IBD vaccine and groups B, C, D and E were infected with 1LD50 IBD virus (10-3.4 in 0.08ml PBS) via conjuctival instillation at 4 week-old. Clinical signs, mortality and gross pathological lesions were scored. Histopathological lesions in bursae of Fabricius were recorded. Virus antibody titre in serum was assayed at 1 day-old, 4 and 6 weeks-old using quantitative agar gel immunodiffusion test. Data generated was analysed using descriptive statistics, ANOVA and Duncan’s multiple comparison tests (P<0.05). Results: The two infected garlic groups B (non-vaccinated) and C (vaccinated) had lower scores for clinical signs (23 and 12 points, respectively) but higher mortality rates (30% and 25%, respectively) than their no-garlic controls (E; 27 points, 11.8% and D; 21 points, 0%, respectively). However, vaccinal antibody response at 6 week-old, was significantly higher in garlic group A (2.8±0.8) than in no-garlic group F (1.8±1.8) in the absence of infection. Conclusion: A more acute outcome of IBD virus infection was observed in garlic-fed broilers, which was ameliorated in vaccinated broilers, however, antibody response to vaccination was enhanced in the absence of infection. http://doi.org/10.5455/javar.2018.e276